Digital single-operator cholangioscopy in diagnostic and therapeutic bilio-pancreatic diseases: A prospective, multicenter study. Issue 9 (September 2022) - Fugazza, Alessandro; Gabbiadini, Roberto; Tringali, Andrea; De Angelis, Claudio Giovanni; Mosca, Piergiorgio; Maurano, Attilio; Di Mitri, Roberto; Manno, Mauro; Mariani, Alberto; Cereatti, Fabrizio; Bertani, Helga; Sferrazza, Sandro; et al.
Abstract: Background and aim: Digital single-operator cholangioscopy (D-SOC) is an endoscopic procedure that is increasingly used for the management of bilio-pancreatic diseases. We aimed to investigate the efficacy and safety of D-SOC for diagnostic and therapeutic indications. Methods: This is a multicenter, prospective study(January 2016-June 2019) across eighteen tertiary centers. The primary outcome was procedural success of D-SOC. Secondary outcomes were: D-SOC visual assessment and diagnostic yield of SpyBite biopsy in cases of biliary strictures, stone clearance rate in cases of difficult biliary stones, rate of adverse events(AEs) for all indications. Results: D-SOC was performed in 369 patients (201(54, 5%) diagnostic and 168(45, 5%)therapeutic). Overall, procedural success rate was achieved in 360(97, 6%) patients. The sensitivity, specificity, PPV, NPV and accuracy in biliary strictures were: 88, 5%, 77, 3%, 83, 3%, 84, 1% and 83, 6% for D-SOC visual impression; 80, 2%, 92, 6%, 95, 1%, 72, 5% and 84, 7% for the SpyBite biopsy, respectively. For difficult biliary stones, complete duct clearance was obtained in 92, 1% patients (82, 1% in a single session). Overall, AEs occurred in 37(10%) cases.The grade of AEs was mild or moderate for all cases, except one which was fatal. Conclusion: D-SOC is effective for diagnostic and therapeutic indications.Most of the AEs were minor and managed conservatively, even though a fatal event has happened that is not negligible and should be considered before using D-SOC.